Effectiveness of Acceptance and Commitment Therapy on Occupational Stress and Anxiety of Nurses Caring for Patients With COVID-19 in Tehran - Hasan Mosazadeh (Shahid Beheshti University of Medical Sciences, 2021)
Background: This research aims to evaluate the impact of acceptance and commitment therapy (ACT) on the occupational stress and the anxiety of nurses. Methods: This was an experimental study with pre-test post-test design with a control group. We included all nurses caring for patients with COVID-19 in governmental hospitals in Tehran during six months of 2020. Beck’s Anxiety Inventory (BAI) and Steinmetz Occupational Stress Questionnaire were used for data collection. Results: Box’s test (P=0.225) showed that the covariance-variance matrices were homogeneous. Levine’s test also indicated that the assumption of variance equality was observed. The amounts of ETA square root showed that 66.3% of the anxiety variance and 51.3% of the occupational stress variance could be predicted in the posttest through ACT. Conclusion: The rate of occupational stress and anxiety of the test group significantly decreased compared with the control group after the intervention. Therefore, ACT could decrease the occupational stress and anxiety of nurses and the therapists could use this approach for improving the mental health of nurses.